Answer:
2,5,8,11
Explanation:
If n=1, 3n-1 =3*1-1 =3-1 =2
If n=2, 3n-1 =3*2-1 =6-1 =5
If n=3, 3n-1 =3*3-1 =9-1 =8
If n=4, 3n-1 =3*4-1 =12-1 =11
We are given the rule [ f(n) = 3n - 1 ] and n represents the term.
First term:
f(n) = 3n - 1
f(1) = 3(1) - 1
f(1) = 3 - 1
f(-1) = 2
Second term:
f(2) = 3(2) - 1
f(2) = 6 - 1
f(2) = 5
Third term:
f(3) = 3(3) - 1
f(3) = 9 - 1
f(3) = 8
Fourth term:
f(4) = 3(4) - 1
f(4) = 12 - 1
f(4) = 11
As you can see, the common difference is 3.
Best of Luck!
5.2m questions
6.7m answers